A Qualitative Evaluation of Web-Based Cancer Care Quality Improvement Toolkit Use in the Veterans Health Administration. Issue 3 (July 2015) - Bowman, Candice; Luck, Jeff; Gale, Randall C.; Smith, Nina; York, Laura S.; Asch, Steven
Abstract : Background: Disease severity, complexity, and patient burden highlight cancer care as a target for quality improvement (QI) interventions. The Veterans Health Administration (VHA) implemented a series of disease-specific online cancer care QI toolkits. Objectives: To describe characteristics of the toolkits, target users, and VHA cancer care facilities that influenced toolkit access and use and assess whether such resources were beneficial for users. Methods: Deductive content analysis of detailed notes from 94 telephone interviews with individuals from 48 VHA facilities. We evaluated toolkit access and use across cancer types, participation in learning collaboratives, and affiliation with VHA cancer care facilities. Results: The presence of champions was identified as a strong facilitator of toolkit use, and learning collaboratives were important for spreading information about toolkit availability. Identified barriers included lack of personnel and financial resources and complicated approval processes to support tool use. Conclusions: Online cancer care toolkits are well received across cancer specialties and provider types. Clinicians, administrators, and QI staff may benefit from the availability of toolkits as they become more reliant on rapid access to strategies that support comprehensive delivery of evidence-based care. Toolkits should be considered as a complement to other QI approaches.